2009
DOI: 10.1016/j.jadohealth.2009.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Nonmedical Use of Prescription Medications and Other Problem Behaviors

Abstract: Purpose-This study examines adolescent nonmedical use of prescription medications (NUPM) and its relationship to other problem behaviors.Methods-A secondary analysis was conducted with data gathered from 912 adolescents in 2007. Four mutually exclusive groups were created from the data. Adolescents who: 1) did not use controlled prescription medications (non-users); 2) used their own controlled medications as prescribed (medical-users); 3) engaged in nonmedical use for self-treatment motivations (selftreaters)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
81
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 30 publications
5
81
1
3
Order By: Relevance
“…Estos datos coinciden con lo reportado por otros autores. Se encontró que la automedicación era un problema presente en la población estudiada 13,14 .…”
Section: Discussionunclassified
“…Estos datos coinciden con lo reportado por otros autores. Se encontró que la automedicación era un problema presente en la población estudiada 13,14 .…”
Section: Discussionunclassified
“…Our findings are consistent with other, smaller studies that have found associations between NMUPD and SRBs. [17][18][19][20][21][22] When we investigated interactions between demographic characteristics and the association between NMUPD and SRBs, we observed significant subgroup differences among sex and racial/ ethnic subgroups, but not grade, for several SRBs. The interaction results for race/ethnicity for NMUPD and SRBs is likely due to two factors: black students have a low prevalence of NMUPD compared with white and Hispanic students and also have a higher prevalence of SRBs such as having had sex, having ≥4 lifetime sexual partners, and being currently sexually active.…”
Section: Discussionmentioning
confidence: 91%
“…[9][10][11][12][13][14][15][16][17] The few studies that exist focused on special populations such as homeless youth or were conducted in small geographic or clinical settings. [17][18][19] One such study surveyed sexually active adolescents and young adults aged 14 to 20 years in an emergency department setting and observed an association between each class of prescription drugs (stimulants, opioids, and sedatives) and SRBs. 17 Adolescents who used >1 class of prescription drugs were significantly more likely to report inconsistent condom use, multiple sexual partners, and substance use before sexual intercourse.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…De modo similar a lo reportado por otros investigadores, las mujeres en nuestro estudio se automedican en mayor proporción que los hombres 18,19 . Sin embargo, un estudio de Evans y Sullivan no reportaron diferencias en cuanto al sexo en la automedicación de psicofármacos 20 .…”
Section: Discussionunclassified